Clive Barker dark imaginer - Ní Fhlainn, Sorcha, 1980- (Manchester University Press, 2017)
Clive Barker: Dark imaginer explores the diverse literary, film and visionary creations of the polymathic and influential British artist Clive Barker. In this necessary and timely collection, innovative essays by leading scholars in the fields of literature, film and popular culture explore Barker's contribution to gothic, fantasy and horror studies, interrogating his creative legacy. The volume consists of an extensive introduction and twelve groundbreaking essays that critically reevaluate Barker's oeuvre. These include in-depth analyses of his celebrated and lesser known novels, short stories, theme park designs, screen and comic book adaptations, film direction and production, sketches and book illustrations, as well as responses to his material from critics and fan communities. Clive Barker: Dark imaginer reveals the breadth and depth of Barker's distinctive dark vision, which continues to fascinate and flourish.
In-house editor: Matthew Frost.
Available through ManchesterHive.
Keywords: Barker, Clive, -- 1952-; Barker, Clive, -- 1952- -- Criticism and interpretation.; Gothic fiction (Literary genre), English -- History and criticism.; LITERARY CRITICISM / Gothic & Romance.; Gothic fiction (Literary genre), English; Criticism, interpretation, etc.